DISKRIMINASI HUKUM DALAM PRINSIP KESETARAAN DI HADAPAN HUKUM BAGI KELOMPOK MINORITAS - Qurrotul Uyun; Nur Ika Mauliyah (Fakultas Hukum, Universitas Islam Balitar, 2026)
The principle of equality before the law is one of the main pillars of the rule of law, guaranteeing equal treatment for all citizens without discrimination. However, in practice, this principle is often not optimally implemented, especially for minority groups who are in vulnerable social, political, and legal positions. This article analyzes the forms of legal discrimination experienced by minority groups in the application of the principle of equality before the law and identifies the factors that cause this inequality. This study uses a normative legal research method with a legislative, conceptual, and case-based approach. The results show that legal discrimination against minority groups occurs in both the substance of the law, the structure of law enforcement, and the legal culture of society. Factors such as bias among law enforcement officials, weaknesses in legal protection, and the influence of social stigma and identity politics are the main obstacles to the realization of substantive legal equality. This article argues that the principle of equality before the law is not sufficient in itself; it must be realized through a substantive approach that protects human rights and ensures justice for minority groups.